2010
DOI: 10.1038/ajh.2010.103
|View full text |Cite
|
Sign up to set email alerts
|

Simvastatin Reduces Pressor Response to Centrally Administered Angiotensin II

Abstract: The results show that simvastatin reduces the pressor response to ICV-infused Ang II in rats. This implies that statins may affect the central regulation of the circulatory system, especially when the brain angiotensin system is stimulated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 17 publications
2
11
0
Order By: Relevance
“…In the present study we found that simvastatin treatment reduces pressor responses to centrally infused AngII, which is in line with previous observations . However, in contrast with our previous study, the antihypertensive effect of simvastatin was associated with a reduction in blood cholesterol. This discrepancy most likely results from differences in simvastatin treatment regimens between the two studies.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In the present study we found that simvastatin treatment reduces pressor responses to centrally infused AngII, which is in line with previous observations . However, in contrast with our previous study, the antihypertensive effect of simvastatin was associated with a reduction in blood cholesterol. This discrepancy most likely results from differences in simvastatin treatment regimens between the two studies.…”
Section: Discussionsupporting
confidence: 92%
“…To exclude peripheral actions of the compounds under investigation, we used the lowest doses of AngII (10 ng) and VP (20 ng) that were sufficient to cause significant hypertensive responses when given i.c.v. but did not affect mean arterial blood pressure (MABP) or heart rate (HR) when infused intravenously . Similarly, we infused 10 μg losartan and 400 ng d(CH 2 ) 5 [Tyr(Me) 2 ,Ala‐NH 2 9 ]VP because these doses have been found to abolish pressor responses to centrally, but not peripherally, administered AngII and VP, respectively …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Circulating Ang II stimulates production and release of adrenal aldosterone, and an increase in hypothalamic aldosterone may also reflect uptake from the circulation, 12 despite its poor penetration. 13 Direct central infusion of Ang II also causes sympathetic hyperactivity 14 and hypertension, 14,15 and may be a more specific stimulus for CNS aldosterone synthesis.…”
mentioning
confidence: 99%